Differential diagnosis of sexual pain in women (La diagnosi differenziale del dolore sessuale nella donna) - Giancarlo Carli, MD; Anna Ghizzani, MD (Publiediting, 2013)
Dyspareunia, a pain that occurs in response to an attempted vaginalentry or to a sexual intercourse, is a clinical entity that recognizes multifactorial etiology. It may be due to organic diseases or to functional disorders suchas Hypoactive Syndrome Desire Disease (HSDD), vaginismus and provoked vulvodynia (PVD). A full history is fundamental for the diagnosis of functional syndromes. For PVD diagnosis, the gynaecologist must also have experience of syndromes of chronic widespread pain of unknownetiology such as fibromyalgia since these syndromes are frequently associated. In PVD local and diffuse hyperalgesia is associated with mechanismsof central sensitization. In PVD there is evidence suggesting local mechanisms of neuropathic nature, although local symptoms consist only in light erythema and oedema.